Metalloalkoxysiloxanes-cured polydimethylsiloxane compositions filled with silica component for special applications: Dielectric and mechanical properties - Alexander N. Tarasenkov; Maria S. Parshina; Nadezhda A. Tebeneva; Kirill M. Borisov; Galina P. Goncharuk; Vitaliy G. Shevchenko; Sergey A. Ponomarenko; Aziz M. Muzafarov (eXPRESS Polymer Letters)
The dielectric and mechanical properties of a wide range of polydimethylsiloxane-based compositions filled with silica component and cured with various metallosiloxanes have been studied. It is shown that the resulting systems are typical dielectrics. Silica component introduction in combination with the metal-siloxane network formation in the material can significantly increase its dielectric permittivity and conductivity in the frequency range <102 Hz compared to commercial silicon compounds and pure PDMS. It is found that varying the metallosiloxane structure and composition and the degree of silica filling are effective tools for changing the dielectric parameters of the material - up to ~5–10 at 1–10 Hz. By varying the functionality and length of the rubber chain, as well as the curing rate, it is possible to vary the mechanical properties of the material within a wide range – 2–10 MPa strength and elongation up to 500% with the pure elastomeric properties up to 200%. This approach to the formation of material opens up prospects for using such cured systems as dielectric elastomers for special applications such as flexible capacitive sensors or actuators for medical and robotic applications.